1998
DOI: 10.1093/emboj/17.7.2019
|View full text |Cite
|
Sign up to set email alerts
|

UTF1, a novel transcriptional coactivator expressed in pluripotent embryonic stem cells and extra-embryonic cells

Abstract: Corresponding author A.Okuda and A.Fukushima contributed equally to this workWe have obtained a novel transcriptional cofactor, termed undifferentiated embryonic cell transcription factor 1 (UTF1), from F9 embryonic carcinoma (EC) cells. This protein is expressed in EC and embryonic stem cells, as well as in germ line tissues, but could not be detected in any of the other adult mouse tissues tested. Furthermore, when EC cells are induced to differentiate, UTF1 expression is rapidly extinguished. In normal mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
156
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(169 citation statements)
references
References 77 publications
7
156
0
5
Order By: Relevance
“…The most differentially regulated phosphopeptides with adj P ‐values of 0.009, 0.017 and 0.019, respectively, were microtubule‐associated protein 1B (Map1B), Jumonji domain containing 1C (Jmjd1c) and p90 ribosomal S6 kinase 1 (RSK1, Rps6ka1 ), all in fraction S1. In N1, increased phosphorylation of pluripotency‐associated transcription factor Utf1 51 was prominent.…”
Section: Resultsmentioning
confidence: 99%
“…The most differentially regulated phosphopeptides with adj P ‐values of 0.009, 0.017 and 0.019, respectively, were microtubule‐associated protein 1B (Map1B), Jumonji domain containing 1C (Jmjd1c) and p90 ribosomal S6 kinase 1 (RSK1, Rps6ka1 ), all in fraction S1. In N1, increased phosphorylation of pluripotency‐associated transcription factor Utf1 51 was prominent.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2A, we confirmed that nucleostemin expression from the Rosa26 locus was rapidly downregulated upon addition of doxycycline to the culture medium. However, the expression levels of pluripotent markers, such as Oct-3/4 [27,32] and UTF1 [25], were unaffected at both the RNA ( Fig. 2A) and protein ( Fig.…”
Section: Pluripotent Marker Expression Was Preserved In Nucleostemin mentioning
confidence: 98%
“…Before performing PCR with the RT products, the number of reaction cycles was determined to achieve semiquantitative conditions with control DNA for each primer set. For western blot analysis, extract treated with sample buffer was used to detect specific protein by chemiluminescence, as described previously [25].…”
Section: Rna and Protein Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We also performed RT-PCR assays to analyze expression of Pou5f1, the activity of which is essential for the identity of the pluripotent cell population in mammalian embryos (Nicols et al, 1998), and Pecam1, Utf1, Cd9, Zfp42, and Spp1, which are expressed in undifferentiated ES cells (Botquin et al, 1998;Hosler et al, 1989;Oka et al, 2002;Okuda et al, 1998;Robson et al, 2001). As shown in Figure 2a, alkaline phosphatase activity was present in colonies composed of ES-like cells on a feeder layer with no activity (Fig.…”
Section: Expression Of Pluripotent Marker Gene On Putative Es Cellsmentioning
confidence: 99%